PENGABDIAN MASYARAKAT BERBASIS PPKN: MENUMBUHKAN KEPEDULIAN LINGKUNGAN DAN GOTONG ROYONG MELALUI GERAKAN BERSIH LORONG - saifuddin, saifuddin; Agus, Andi Aco; Amirullah, Amirullah; Bustam, Bustam; Watif Massuanna, Muhammad (Program Studi Manajemen FEB UNM, 2025)
This community service program was carried out with the aim of fostering environmental awareness and strengthening the spirit of mutual cooperation among residents through the Bersih Lorong (Clean Alley) activity. The program is grounded in the perspective of Civic and Pancasila Education (PPKn), which emphasizes the importance of shared responsibility, solidarity, and active citizen participation in community life. The background of this initiative stems from the poorly maintained condition of the alley environment, which required a collective effort to create a clean, healthy, and comfortable living space. The implementation methods included the socialization of relevant PPKn values, community empowerment in planning activities, and joint community work to clean the alley. Active participation of residents served as an indicator of success, as the community not only engaged in cleaning activities but also demonstrated stronger environmental concern and solidarity. The results of the program showed an increased awareness of the importance of maintaining a clean environment, the creation of a cleaner alley condition, and the development of a more internalized habit of mutual cooperation in daily life. Therefore, this activity not only had a physical impact on the environment but also strengthened the character values of the community in line with the goals of civic education. Keywords: Community Service, Civic and Pancasila Education, Mutual Cooperation, Environmental Awareness, Clean Alley